DO3SE modelling of soil moisture to determine ozone flux to forest trees - Büker, P.; Morrissey, T.; Briolat, A.; Falk, R.; Simpson, D.; Tuovinen, J.-P.; Alonso, R.; Barth, S.; Baumgarten, M.; Grulke, N.; Karlsson, P. E.; King, J.; et al. (Atmospheric Chemistry and Physics, 2012)
The DO3SE (Deposition of O3 for Stomatal Exchange) model is an established tool for estimating ozone (O3) deposition, stomatal ﬂux and impacts to a variety of vegetation types across Europe. It has been embedded within the EMEP (European Monitoring and Evaluation Programme) photochemical model to provide a policy tool capable of relating the ﬂux-based risk of vegetation damage to O3 precursor emission scenarios for use in policy formulation. A key limitation of regional ﬂux-based risk assessments has been the assumption that soil water deﬁcits are not limiting O3 ﬂux due to the unavailability of evaluated methods for modelling soil water deﬁcits and their inﬂuence on stomatal conductance (gsto), and subsequent O3 ﬂux. This paper describes the development and evaluation of a method to estimate soil moisture status and its inﬂuence on gsto for a variety of forest tree species. This DO3SE soil moisture module uses the Penman-Monteith energy balance method to drive water cycling through the soil-plantatmosphere system and empirical data describing gsto relationships with pre-dawn leaf water status to estimate the biological control of transpiration. We trial four different methods to estimate this biological control of the transpiration stream, which vary from simple methods that relate soil water content or potential directly to gsto, to more complex methods that incorporate hydraulic resistance and plant capacitance that control water ﬂow through the plant system. These methods are evaluated against ﬁeld data describing a variety of soil water variables, gsto and transpiration data for Norway spruce (Picea abies), Scots pine (Pinus sylvestris), birch (Betula pendula), aspen (Populus tremuloides), beech (Fagus sylvatica) and holm oak (Quercus ilex) collected from ten sites across Europe and North America. Modelled estimates of these variables show consistency with observed data when applying the simple empirical methods, with the timing and magnitude of soil drying events being captured well across all sites and reductions in transpiration with the onset of drought being predicted with reasonable accuracy. The more complex methods, which incorporate hydraulic resistance and plant capacitance, perform less well, with predicted drying cycles consistently underestimating the rate and magnitude of water loss from the soil. A sensitivity analysis showed that model performance was strongly dependent upon the local parameterisation of key model drivers such as the maximum gsto, soil texture, root depth and leaf area index. The results suggest that the simple modelling methods that relate gsto directly to soil water content and potential provide adequate estimates of soil moisture and inﬂuence on gsto such that they are suitable to be used to assess the potential risk posed by O3 to forest trees across Europe.
Keywords: DO3SE; Drought (voyant); Modeling; soil water; Stomatal conductance; Stomatal ozone ﬂux

Stomatal conductance of semi-natural Mediterranean grasslands: implications for the development of ozone critical levels. - Alonso, R.; Bermejo, V.; Sanz, J.; Valls, B.; Elvira, S.; Gimeno, B. S. (Environmental pollution (Barking, Essex : 1987), 2007)
Intra-genus and intra-specific variation and the influence of nitrogen enrichment on net assimilation and stomatal conductance of some annual Trifolium species of Mediterranean dehesa grasslands were assessed under experimental conditions. Also gas exchange rates were compared between some Leguminosae and Poaceae species growing in the field in a dehesa ecosystem in central Spain. The results showed that the previously reported different O3 sensitivity of some Trifolium species growing in pots does not seem to be related to different maximum g(s) values. In addition, no clear differences on gas exchange rates could be attributed to Leguminosae and Poaceae families growing in the field, with intra-genus variation being more important than differences found between families. Further studies are needed to increase the database for developing a flux-based approach for setting O3 critical levels for semi-natural Mediterranean species.
The following values have no corresponding Zotero field: accession-num: 16895740
Keywords: Critical levels; Grasslands; Ozone; Semi-natural vegetation; Stomatal conductance